2013
DOI: 10.1016/j.neuroscience.2013.05.037
|View full text |Cite
|
Sign up to set email alerts
|

A spontaneous state of weakly correlated synaptic excitation and inhibition in visual cortex

Abstract: Cortical spontaneous activity reflects an animal’s behavioral state and affects neural responses to sensory stimuli. The correlation between excitatory and inhibitory synaptic input to single neurons is a key parameter in models of cortical circuitry. Recent measurements demonstrated highly correlated synaptic excitation and inhibition during spontaneous “up-and-down” states, during which excitation accounted for approximately 80% of inhibitory variance (Shu et al., 2003; Haider et al., 2006). Here we report i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 92 publications
3
21
0
Order By: Relevance
“…Since it was first proposed that excitatory/inhibitory ( E / I ) balance emerges within brain networks (van Vreeswijk & Sompolinsky, ), a large body of theoretical and experimental work has focused on clarifying its regulation and possible role in maintaining desired spatiotemporal activity states (Deneve & Machens, ). Co‐occurring E / I responses have been observed for many modalities, for example, in auditory cortex (D'Amour & Froemke, ; Wehr & Zador, ), visual cortex (Liu et al, ; Tan, Andoni, & Priebe, ) and olfactory cortex (Poo & Isaacson, ; Stettler & Axel, ). Besides activity evoked by stimuli, balanced excitation and inhibition also appear to be present during spontaneous brain activity (Graupner & Reyes, ; Murphy & Miller, ) and may play a critical role in generating certain brain rhythms (Atallah & Scanziani, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since it was first proposed that excitatory/inhibitory ( E / I ) balance emerges within brain networks (van Vreeswijk & Sompolinsky, ), a large body of theoretical and experimental work has focused on clarifying its regulation and possible role in maintaining desired spatiotemporal activity states (Deneve & Machens, ). Co‐occurring E / I responses have been observed for many modalities, for example, in auditory cortex (D'Amour & Froemke, ; Wehr & Zador, ), visual cortex (Liu et al, ; Tan, Andoni, & Priebe, ) and olfactory cortex (Poo & Isaacson, ; Stettler & Axel, ). Besides activity evoked by stimuli, balanced excitation and inhibition also appear to be present during spontaneous brain activity (Graupner & Reyes, ; Murphy & Miller, ) and may play a critical role in generating certain brain rhythms (Atallah & Scanziani, ).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of recurrent inhibitory and excitatory circuits also regulates the occurrence of cortical up and down states (Haider, Duque, Hasenstaub, & McCormick, ; Shu, Hasenstaub, & McCormick, ), and it was shown that different levels of correlation between excitation and inhibition can emerge from the same neuronal circuitry, depending on the specific cortical state—with correlations observed to be lower during anesthesia than during states exhibiting up and downstate activity (Tan et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Tan et al (2013) proposed a methodology to calculate the Pearson correlation of excitatory and inhibitory SCs from stationary data based on the dependency of the variance of membrane current on holding potential. This approach is distinct from MtKF because MtKF infers the full time course of conductances as opposed to only certain statistics.…”
Section: Discussionmentioning
confidence: 99%
“…Testing this model prediction directly might be difficult, as it is hard to isolate excitatory and inhibitory inputs onto a single neuron simultaneously. However, the observed arrangement makes the prediction that the magnitude of temporal fluctuations in membrane potential measured at the reversal of either excitation or inhibition should be much larger than those measured at normal operating potentials, which can be tested (Tan et al, 2013).…”
mentioning
confidence: 98%